2017
DOI: 10.4172/neuropsychiatry.1000300
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteome Analysis of Catatonia

Abstract: The exact mechanism of catatonia remains a mystery. We tried to investigate the serum biomarkers for patients with catatonia before and after successful treatment using proteomic analysis. During a three-year period, nine patients with schizophrenia who experienced catatonia and nine healthy controls were recruited. 5 ml of venous blood were collected before (acute phase) and after treatment (recovery phase) of catatonia, relieved by intramuscular lorazepam injection. The serum proteomes of acute and recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Besides, it is known that the catatonia symptoms can reflect the extreme severity of affective deficit (48). According to other studies patients with schizophrenia accompanied by catatonic symptoms are found to have lower serum BDNF levels (49,50), which proves the link between BDNF and catatonia symptoms (51). According to findings of other researcher, motor functions significantly correlate with cognitive function in patients with schizophrenia (52).…”
Section: Discussionmentioning
confidence: 86%
“…Besides, it is known that the catatonia symptoms can reflect the extreme severity of affective deficit (48). According to other studies patients with schizophrenia accompanied by catatonic symptoms are found to have lower serum BDNF levels (49,50), which proves the link between BDNF and catatonia symptoms (51). According to findings of other researcher, motor functions significantly correlate with cognitive function in patients with schizophrenia (52).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, there was no significant difference between serum iron levels during and between catatonic episodes which could indicate an underlying vulnerability, according to the authors [15]. Other research has suggested that the serum amyloid P component could be a potential diseaseassociated biomarker for catatonia [16]. In the largest study of catatonia neuroimaging on psychiatric inpatients to date, it was found that magnetic resonance imaging (MRI) scan abnormalities were common in patients with catatonia, and mostly consisted of diffuse cerebral atrophy rather than focal lesions.…”
Section: Introductionmentioning
confidence: 92%